Mvanʻ Praññʻ nayʻ Kyuikʻ thui Mruiʹ Mahā Muni Svanʻʺ Bhu rāʺ krīʺ samuiṅʻʺ : nhacʻ 100 praññʻʹ ʼa thimʻʺ ʼa mhatʻ, 1256-1356 (Thuikʻ Cā pe ; Phranʻʹ khyi reʺ, Mahā Muni Svanʻʺ Bhu rāʺ krīʺ Gopaka ʼA phvaiʹ, 1994)
About Buddhist shrine Mahā Muni Svanʻʺ Bhu rāʺ in Kyaikto, Burma.